Trust in Educational Settings—What It Is and Why It Matters. European Perspectives. Issue 3 (2nd October 2021) - Bormann, Inka; Niedlich, Sebastian; Würbel, Iris
Abstract: This editorial paper introduces the relevance of trust in educational settings. It discusses interdisciplinary approaches to trust, reflects upon the relationships between trust and education and how trust has so far been studied in educational research. In addition, a comprehensive model of trust is introduced as a framework for the individual papers of this special issue that altogether, through different disciplinary and methodological lenses, investigate trust in various realms of education in five European countries.